Cost of Farm Operations for Major Cereals in Nigeria - Fadlullah Olayiwola Issa (Journal of Agricultural Extension, 2023)
This study assessed the cost of farm operations for major cereals in Nigeria. Secondary data obtained from the annual agricultural performance survey of the National Agricultural Extension and Research Liaison Services (NAERLS) was used to compute the cost of 12 farm operations as well as the percentage change in the cost from 2021 to 2022. Results showed that the cost of farm operations for producing major cereals recorded a very high increase across the states in Nigeria. The mean cost of farm operations for producing a hectare of rice in Nigeria was estimated to be ?343,339, while that of maize was ?296,027. However, the percentage increase in the cost of farm operations for producing a hectare was higher for maize (25.4%) than rice (18.3%). Furthermore, the percentage increase in the cost of farm operations for producing a hectare of maize was higher in the Northern region (34.9%) than in the South (17.2%). For rice, the percentage increase was higher in the Southern region (21.8%) than in the North (13.7%). The cost of farm operations have generally increased thereby threatening food prices. Efficient tractor-hiring services should be made available at subsidized rates at all LGAs through public-private partnership arrangements in Nigeria.